Biodiesel Production From Lignocellulosic Biomass Using Oleaginous Microbes: Prospects for Integrated Biofuel Production - Chintagunta, Anjani Devi; Zuccaro, Gaetano; Kumar, Mahesh; Kumar, S. P. Jeevan; Garlapati, Vijay Kumar; Postemsky, Pablo D.; Kumar, N. S. Sampath; Chandel, Anuj K.; Simal-Gandara, Jesus (Frontiers in Microbiology, 2021)
Biodiesel is an eco-friendly, renewable and potential liquid biofuel in mitigating green house gas emissions. Biodiesel has been produced initially from vegetable oils, non-edible oils and waste oils. However, these feedstocks have several disadvantages such as requirement of land, labour and remains expensive. Similarly, in reference to waste oils, the feedstock content is succinct in supply and unable to meet the demand. Recent studies demonstrated utilization of lignocellulosic substrates (LCS) for biodiesel production using oleaginous microorganisms. These microbes accumulate higher lipid content under stress conditions, whose lipid composition is similar to vegetable oils. In this paper, steps enumerated in biodiesel production from lignocellulosic substrates through pretreatment, sachharification and oleaginous microbes mediated fermentation, lipid extraction, transesterification and purification of biodiesel are illustrated. Besides, a note on integration of liquid biofuels has been included that have significant importance in terms of circular economy aspects. Adoption of this process would lead to development of cost-effective process that can utilize every by-product of the process.